Pro- and Anti-Inflammatory Cytokines Release in Mice Injected with Crotalus durissus terrificus Venom - A. Hernández Cruz; S. Garcia-Jimenez; R. Zucatelli Mendonça; V. L. Petricevich (Hindawi Limited, 2008)
The effects of Crotalus durissus terrificus venom (Cdt) were analyzed with respect to the susceptibility and the inflammatory mediators in an experimental model of severe envenomation. BALB/c female mice injected intraperitoneally presented sensibility to Cdt, with changes in specific signs, blood biochemical and inflammatory mediators. The venom induced reduction of glucose and urea levels and an increment of creatinine levels in serum from mice. Significant differences were observed in the time-course of mediator levels in sera from mice injected with Cdt. The maximum levels of IL-6, NO, IL-5, TNF, IL-4 and IL-10 were observed 15 min, 30 min, 1, 2 and 4 hours post-injection, respectively. No difference was observed for levels of IFN-γ. Taken together, these data indicate that the envenomation by Cdt is regulated both pro- and anti-inflammatory cytokine responses at time-dependent manner. In serum from mice injected with Cdt at the two first hours revealed of pro-inflammatory dominance. However, with an increment of time an increase of anti-inflammatory cytokines was observed and the balance toward to anti-inflammatory dominance. In conclusion, the observation that Cdt affects the production of pro- and anti-inflammatory cytokines provides further evidence for the role played by Cdt in modulating pro/anti-inflammatory cytokine balance.